2006
DOI: 10.1645/ge-873r.1
|View full text |Cite
|
Sign up to set email alerts
|

VARIATION IN HOST SPECIFICITY BETWEEN SPECIES OF AVIAN HEMOSPORIDIAN PARASITES: EVIDENCE FROM PARASITE MORPHOLOGY AND CYTOCHROMEBGENE SEQUENCES

Abstract: A parasite's shift to a new host may have serious evolutionary consequences, since host switching usually is associated with a change in virulence and may lead to the evolution of emerging diseases. This phenomenon remains insufficiently studied in wildlife. Here, we combine microscopic examination of blood films and PCR-based methods to investigate the natural host specificity of Haemoproteus and Plasmodium spp. in birds of 4 families of the Passeriformes within a small geographic area. The material was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
88
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 27 publications
9
88
1
Order By: Relevance
“…In the current study, we identified parasites to species only when ample parasitemia and morphology allowed us to do so with confidence. Nonetheless, we report identifications only as ''consistent with the morphology'' of described species because the union of morphologic and molecular systematics for these parasites is only in its infancy (Krizanauskiene et al, 2006;Martinsen et al, 2006). Collection of birds and blood samples followed protocols of state, federal, and University of California Animal Care and Use permits.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the current study, we identified parasites to species only when ample parasitemia and morphology allowed us to do so with confidence. Nonetheless, we report identifications only as ''consistent with the morphology'' of described species because the union of morphologic and molecular systematics for these parasites is only in its infancy (Krizanauskiene et al, 2006;Martinsen et al, 2006). Collection of birds and blood samples followed protocols of state, federal, and University of California Animal Care and Use permits.…”
Section: Methodsmentioning
confidence: 97%
“…Fallon et al (2005) simply abandon any attempt to identify parasites to species and use gene sequences to score parasite lineages for analysis of host ranges. A prudent combination of morphologic identification with gene sequence data and phylogenetic analysis provides the best picture of host range for hemosporidian parasites and reveals that at least some of the parasite species can infect birds of a broad range of systematic families (Krizanauskiene et al, 2006). All our species identifications are based on examination of many parasites from an infection and are consistent with morphology expected for those species, but in light of studies of parasite morphology and gene sequence data (Martinsen et al, 2006(Martinsen et al, , 2007, we offer our morphologic species identifications as only preliminary in revealing the species-level diversity of hemosporidian parasites in the bird community sampled.…”
Section: Picoides Pubescensmentioning
confidence: 99%
“…Phylogenetic reconstruction of cytochrome b (cytb) lineages from readily distinguishable morphospecies has shown that many lineages form monophyletic clusters that match morphospecies. Such congruence between genetic and morphological data demonstrates the integration of traditional parasitology and molecular biology (Perkins & Schall 2002, Križanauskiené et al 2006, Hellgren et al 2007, Palinauskas et al 2007. However, molecular studies based on both mitochondrial and nuclear DNA have also shown that some morphological and life-history traits within haemosporidian parasites do not necessarily indicate evolutionary coherence (Perkins & Schall 2002, Ricklefs et al 2004, which warrants further investigation.…”
mentioning
confidence: 95%
“…the same species of Plasmodium can develop in birds belonging to several families and even orders, but some species seem to be relatively host restricted (Iezhova et al 2005, Križanauskiené et al 2006, Palinauskas et al 2009, Loiseau et al 2010. For example, the lineage P-SGS1 of Plasmodium relictum is a generalist and has been found in over 40 species of birds belonging to several families of the order Passeriformes.…”
mentioning
confidence: 99%
“…New insights are being gained from the rapidly increasing volume of DNA sequencing work which provides genetic information such as cytochrome b gene sequences for classically named parasites. The question of how this new information reinforces or refutes the old taxonomic order is the focus of current stimulating research (Fallon et al, 2003Martinsen et al, 2006;Krizanauskiene et al, 2006;Hellgren et al, 2007). It is impossible to predict the ultimate conclusions, yet some trends are emerging.…”
mentioning
confidence: 99%